Robert Ludlum's The Bourne enigma : [large type] a new Jason Bourne novel - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2016)
On the eve of Russian General Boris Karpov's wedding, Jason Bourne receives an enigmatic message from his old friend and fellow spymaster. In Moscow, what should be a joyous occasion turns bloody and lethal. Now Bourne is the only one who can decipher Karpov's cryptogram. He discovers that Karpov was willing to betray his Sovereign to warn Bourne of a crippling disaster about to be visited on the world. Bourne has only four days to discover the nature of the disaster and stop it. The trail Karpov has been following leads Bourne to Cairo and the doorstep of Ivan Borz, the elusive international arms dealer infamous for hiding behind a never-ending series of false identities, a man Bourne has been hunting ever since Borz abducted former Treadstone director Soraya Moore and her two-year-old daughter, and brutally murdered her husband.